Adaptive Governance or Status Quo? Unpacking the City of Jakarta's Approach to the Air Pollution Control Program - Arrozaaq, Dimas Luqito Chusuma; Firmansyah, M. Irwanda (Universitas Airlangga, 2023)
In recent years, Jakarta has experienced an increase in air pollution which has the potential to have a significant impact on Jakarta residents not only in terms of health, but socio-cultural and productivity. This encourages the need for effective governance strategies to overcome air pollution problems. This study seeks to critically analyze the approach used by the city of Jakarta in dealing with air pollution to find out whether the city of Jakarta's air pollution control policy has led to innovative, flexible and adaptive governance, or is still more inclined towards maintaining the status quo. Based on qualitative data, including in-depth interviews, policy analysis, and consultation with stakeholders, this research examines Jakarta's policy mechanisms, community participation pathways, and inter-agency coordination in controlling air quality and dealing with pollution. The research results show a lack of alignment between progressive policy frameworks and implementation challenges, thus underscoring the need for a more adaptive and dynamic approach. The approach adopted in Jakarta appears to be dominated by a top-down, government-led model, where policies and decisions are primarily formulated and implemented with minimal participation from non-governmental institutions. Such models, while ensuring efficient decision making, may exclude valuable insights of other stakeholders and hinder innovative and context-specific solutions. Additionally, these rigid structures appear to lack the flexibility and responsiveness that are hallmarks of adaptive governance, potentially reducing cities' ability to effectively address air pollution challenges. This research underscores the need for a more inclusive and adaptive governance framework in managing air pollution in Jakarta.